Methodology for Preparation of Audit Entities to External Control of the Quality of Audit Services - Lubenchenko О. Ye.; Lysiuk А. V. (Statistics of Ukraine, 2020)
The requirements to the system of control over the quality of audit services are analyzed, which are specified in the Law of Ukraine “Audit of Financial Statements and Auditing” from 21.12.2017 No 2258-VIII; Directive of the Ministry of Finance of Ukraine “Approval of the Procedure for Inspection of the Quality Control of Audit Services” from 29.08.2019 No 362; Resolution of the Council for Supervision over Auditing at the State Institution “The Body of Public Supervision over Auditing” from 30.08.2019 No 6/7/13 “Information Questionnaire of Auditing Entity”. It is demonstrated that the quality control system requires corrections of the following: responsibilities of administration and staff of auditing entities for use of the adopted intra-firm provisions on the quality control system, requirements of ISQC1, IAS, the Law of Ukraine “Audit of Financial Statements and Auditing”; the requirements to staff (quality controller, reviewer, assignment partner); identification of threats to the independence and the auditor’s response on the assessed threats; the requirements to reviews of complaints, complicated issues; issues related with non-stop professional training of auditors. Special attention of auditors need to be drawn to the fact that the policies and procedures of the quality control system do not have to be confined to the audit of financial statements, but have to apply to other assignments on giving confidence and related auditor services. Besides that, assessment of threats to the independence has to be conducted for non-auditor services specified in Article 6 of the aforementioned Law of Ukraine. The studies conducted by the author allowed to elaborate procedures for quality control of auditor services; measures to stimulate staff of auditing entities to scrutinize requirements to implementation of the quality control system; obligating documents of auditing firms on assessment of ethical threats; sharing of duties among assignment group members; requirements to qualification of the key partner, quality controller; identification of auditor assignments; solutions of complicated issues and their documenting, measures on control of the assignment at the final phase and quality control of the assignment. The proposed measures are supposed to help auditing entities revise the already operating quality control systems in a timely manner, which will facilitate supply of high quality information to all the users of auditing reports, external quality controllers from the Body of Public Supervision over Auditing and the Auditor Chamber of Ukraine.